KAJIAN PENDIDIKAN NILAI MORAL MELALUI PROGRAM LIVING VALUES ACTIVITIES DALAM PENGEMBANGAN KARAKTER SISWA - Hayati, Auliya Aenul (2015)
SMA Plus Muthahhari come with the Living Values Activities program which is full of living values. The results showed: (1).The moral values education contents through LVA program consists of Personal Development Program,X-Day,Dirasah Islamiyyah; (2).The moral values education method through LVA program consists of using the general method, special method, integrated model; (3).The moral values education process through LVA program covering by the phase of Value Identification, Activity, Learning Aids, Interactions Unit, Segment and Evaluation; (4).The problem of Values Education through LVA Program is a complex moral value measurements, the rules of moral values is not Perfectly executed, the less time; (5).The follow-up moral values education problem through the LVA program: bring students on real life conditions that are different from their daily life, held a sustainable menu system, Improving communication between the parties, and optimizing moral values education quality.